PTU-033 Negotiation of the splenic flexure- an observational study of patient characteristics and colonoscopic manoeuvres. (17th June 2017) - O'Connor, S; Carr, R; Dunkley, P; Valori, R; Anderson, J
Abstract : Introduction: Successful negotiation of the splenic flexure (SF) during colonoscopy is essential in achieving caecal intubation. Our aim was to assess patient characteristics and colonoscopic manoeuvres (CM) that facilitate insertion through and beyond the SF. Method: We conducted a prospective observational study of colonoscopies performed within 2 high volume national training centres in the United Kingdom (UK) where the average caecal intubation rate is 97%. All colonoscopists were certified for colonoscopy within the UK. Data was collected on a pro-forma which was completed by the colonoscopist or an assistant, during or post colonoscopy. Patient sex, age, body mass index (BMI-kg/m²), history of past major abdominal surgery and sedation used were documented. Magnetic endoscope imager (ScopeGuide, Olympus Medical Systems Corporation, Japan) was used for all procedures to determine scope and tip position at the SF. CM employed, patient position, time and success at each SF pass attempt was recorded. The CM that were recorded included, breath in and hold, mid/lower abdominal pressure, left upper quadrant/flank pressure, slowing down, suction and tip deangulation. Results: 10 colonoscopists recorded data on 158 colonoscopies. 140 (88.6%) of these were performed by Gastroenterologists. 43 (27.2%) colonoscopies were unsedated. No patients had more than 3 mg Midazolam or 100mcg Fentanyl. 123 (77.8%) initial attempts at splenic flexure (SF) passes were successful. Of these successful SF passes, the scope stiffener was used in 81 (65.8%) patients. 76 (61.8%) patients were supine and 31 (25.2%) were in the right lateral position. Additional CM was not used in 84 (68.2%) of these patients. Specific slowing of the scope insertion was the most common CM used for successful 1 st pass and was used in 21 (17.1%) patients. Patients with a BMI >30 kg/m² (obese) were more likely to require >1 attempt at negotiation of the SF compared to BMI <30 kg/m² (non-obese) (42% v 20.2%, p=0.017). Obese patients more often needed additional CM to pass the scope tip beyond the SF (p=0.012). The most successful CM in aiding scope passage in this group of patients was abdominal pressure applied to the left upper quadrant whilst in the supine position (p<0.05). Other CM, positions or patient characteristics did not significantly influence passage of SF. Conclusion: Patient satisfaction and comfort are essential, especially where no or minimal sedation is used in colonoscopy. Left upper quadrant pressure can aid passage through the SF in obese patients. Further studies are needed to determine the optimal patient positions and CM to facilitate comfortable, effective and efficient colonoscopy. Disclosure of Interest: None Declared